2017
DOI: 10.1038/nm.4290
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting CASP8 and FADD-like apoptosis regulator ameliorates nonalcoholic steatohepatitis in mice and nonhuman primates

Abstract: Nonalcoholic steatohepatitis (NASH) is a progressive disease that is often accompanied by metabolic syndrome and poses a high risk of severe liver damage. However, no effective pharmacological treatment is currently available for NASH. Here we report that CASP8 and FADD-like apoptosis regulator (CFLAR) is a key suppressor of steatohepatitis and its metabolic disorders. We provide mechanistic evidence that CFLAR directly targets the kinase MAP3K5 (also known as ASK1) and interrupts its N-terminus-mediated dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
191
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(200 citation statements)
references
References 67 publications
4
191
1
Order By: Relevance
“…Inactivation of c-FLIP L in mouse hepatocytes promotes liver injury triggered by death receptor agonists (39). A recent study demonstrated that AAV-mediated overexpression of c-FLIP L in the liver ameliorates NASH in mice and nonhuman primates (41), illustrating a crucial role of this factor in NASH. However, the physiological and pathophysiological cues that impinge on c-FLIP L remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of c-FLIP L in mouse hepatocytes promotes liver injury triggered by death receptor agonists (39). A recent study demonstrated that AAV-mediated overexpression of c-FLIP L in the liver ameliorates NASH in mice and nonhuman primates (41), illustrating a crucial role of this factor in NASH. However, the physiological and pathophysiological cues that impinge on c-FLIP L remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall experimental design for the cited studies 14,9 in this correspondence challenges the conventional doctrine of previous findings on pre-existing NABs against AAV virus. For example, in the above studies in question, it was not stated whether any of the monkeys were screened for AAV8 NABs.…”
Section: To the Editormentioning
confidence: 89%
“…Recently, Hongliang Li and colleagues 14 published four studies in Nature Medicine applying AAV serotype 8 vectors (AAV8) in nonhuman primate (NHP) models of nonalcoholic steatohepatitis. In each study, genes delivered to the liver via AAV vectors demonstrated transduction in these large animal models, and therapeutic effects were achieved.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phase II data demonstrated reduction of fibrosis without worsening of steatohepatitis after only 24 weeks of GS-4997 treatment in NAFLD patients (76). Caspase-8 and FADD-like apoptosis regulator (CFLAR) has been identified as a key suppressor of NASH that directly blocks ASK1/JNK1 activation (77). Therefore, CFLAR-mimicking drugs represent a novel therapeutic option for fatty liver disease.…”
Section: Similar Pathophysiological Concepts Of Nash and Ash With CLImentioning
confidence: 99%